Evaluation and fMRI Analysis of Cognitive and Language Impairment of Perinatally Acquired Left Brain Injury - Xiuyuan ZHENG; Fenyan HUANG; Tiebin YAN; Lingjun XIAO; Nan YAN; Xiaofeng LIN; Zhiying LIANG (康复学报)
Objective:To explore the effect of perinatally acquired left brain injury on language and cognitive ability by evaluation and fMRI analysis.Methods:The subject for study was a child with perinatally acquired left brain injury.3.0T BOLD fMRI scaned the brain region of the subject when the subject was performing picture naming task to observe activated encephalic region. The Eprime2.0 software was used to design tasks of block-design model, with resting phase (no picture stimulation) and stimulating phase (picture stimulation) in turn. The task required the child to name pictures quietly. Cognitive psychology ability and neurological function were evaluated by Wechsler Intelligence Scale for Children (WISC), somatosensory evoked potential (SEP), motor evoked potential (MEP), electroencephalogram (EEG), MR+MRA+DTI, and Eysenck personality questionnaire (EPQ).Results:Verbal IQ was a little weaker than performance IQ, the difference was not significant. While manipulative skill of the child developed evenly (PVI=4.87), language and total IQ developed unevenly (PVI=18.70, 11.30). fMRI showed activated encephalic region was temporal lobe surrounding left injury region.Conclusion:Language impairment is not obvious in the child with perinatally acquired left brain injury. Temporal lobe surrounding injury region becomes new functional language areas.